Integrasi Keilmuan Islam Madrasah Ibtidaiyah dalam Membentuk Akhlak Generasi Emas - M Choirul Muzaini; Maya Sarita; Sedya Santosa (Peneliti.net, 2023)
The study aims to become material for study and also provide information and also solutions to efforts that can be implemented in the Islamic integration of Islamic elementary schools in shaping the morals of the golden generation. This study uses a qualitative approach with the method of literature (Library Research). Data collection techniques with literature studies and documentation. Data analysis techniques in this study used data reduction, data presentation, and conclusions. And the technique of guaranteeing the validity of the researcher's data uses Source Triangulation. The results of the study found that Islamic elementary school is an Islamic elementary-level educational institution that integrates school and Islamic boarding school education by combining general knowledge and religious knowledge, but the two complement each other without negating the uniqueness of each of these disciplines so that they are able to welcome education. by creating a generation of morals, knowledge, and skills.